Traits of the journalist figure in the first treaties about journalism in Spain. Towards a professional identity (1891-1912) - Rodríguez Rodríguez, Jorge Miguel (2019)
The study analyzes the first journalism textbooks published in Spain between 1891 and 1912, which outline the professional features the reporter in that historical stage should have. Because of its influence on the political, social and cultural regulations, the the journalism activity then claimed a status of its own for itself, which distinguished it from other activities that, as literature, shared the word as an expression tool, and also were published in newspapers and magazines.